Determinación de la huella de carbono para la elaboración del manual de mitigación en la universidad técnica de Cotopaxi, campus la Matriz, periodo 2020-2021. - Herrera Vaca, Bryan David (2021)
This research aimed to determine the carbon footprint and preparation of a mitigation manual at the Technical University of Cotopaxi, "La Matriz" Campus, located in the Eloy Alfaro Parish, Latacunga-Cotopaxi. This study directed to know the amount of annual carbon dioxide emission per individual belonging to the campus "La Matriz," using the accounting accounts method version 2.0 ideal for the detailed calculation of the organizational carbon footprint. It develops a manual for the mitigation of carbon dioxide. Rees and Wackernagel developed the method used in 2000; it has been updated until 2016. The calculation obtained with all the individuals, who are part of the campus, was collected in "La Matriz" with the university community: administrative, teachers, service personnel, and students. The authorities' collaboration was fundamental to obtain the financial department's economic information, control of assets, and human talent. It was also necessary to collect information on specific materials and data not in the institution's system. So, the separate calculations were made using the MC3 method according to the corporate limits and the scope. The results showed in the "La Matriz" campus complies with the Kyoto protocol provisions regarding emissions per individual. Moreover, that is why its Carbon Footprint as an organization does not exceed the emission rate of C02. It is necessary to consider that it is always necessary to mitigate carbon dioxide emissions for the environment and the community's welfare beyond the results.